La lucha contra la desertificación de las tierras en la base del desarrollo sostenible - Mendizábal Aracama, Teresa (Revista Española de Desarrollo y Cooperación, 2023)
The article analyses soil complexity and fragility, as well as its major functions, considered from the environmental, economic, social and cultural standpoints. Desertification is described as the degradation of the land in arid, semi-arid and dry sub-humid areas as a result of the joint action of climate changes and human activities and its consequences for man and his environment are pointed out whilst the United Nations Convention to Combat Desertification is presented. The concept of Sustainable Development, taken as a process of change calling for a continuous effort for adapting the policies involved, is discussed. Finally, it presents the need to protect and conserve soil as the main instrument for eradicating poverty in the framework of sustainable development strategy.